Adhesive
The adhesive, composed of a hydrophilic polymer and a plasticizer with multiple hydroxyl groups, addresses the challenge of maintaining strong adhesion to fine dot patterns while enabling easy water-based removal from non-mask areas in sandblasting processes.
Patent Information
- Application Number
- JP2023169643
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Existing adhesives for mask materials in sandblasting processes face challenges in maintaining strong adhesion to fine dot patterns while allowing easy removal of the adhesive in non-mask portions without damaging the pattern, especially on curved or three-dimensional workpieces.
An adhesive comprising a hydrophilic polymer, such as polyvinylpyrrolidone or a vinylpyrrolidone/vinylacetate copolymer, combined with a plasticizer having two or more hydroxyl groups, which provides strong adhesion to mask patterns and allows easy water-based removal from non-mask areas.
The adhesive effectively maintains the integrity of fine dot patterns during sandblasting and allows for easy and selective removal of the adhesive from non-mask areas using water, addressing the limitations of existing adhesives.
Smart Images

Figure 2025059513000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive used when adhering a mask material for sandblasting to a workpiece. [Background technology]
[0002] Conventionally, when cutting a workpiece such as glass, stone, metal, plastic, ceramic, etc. to form a relief image, processing by sandblasting (hereinafter also referred to as sandblasting) is performed. Sandblasting is a process in which a masking portion is provided on the workpiece using a mask material, and then an abrasive such as sand particles, ceramic particles, metal particles, etc. is sprayed onto the exposed surface of the workpiece to selectively cut the workpiece.
[0003] As a mask material for the above-mentioned sandblasting treatment, for example, a dry film is used which has a photosensitive resin layer on a support such as a polyester film, and a cover film laminated on the photosensitive resin layer.
[0004] In the process of providing the above-mentioned photosensitive resin layer on the workpiece, a method of laminating the photosensitive resin layer by thermocompression is known. For example, Patent Document 1 and Patent Document 2 describe a method of thermocompression bonding by laminating a photosensitive resin composition layer on a workpiece heated to an arbitrary temperature using a rubber roller or the like. Patent Document 3 describes a method of thermocompression bonding by laminating a photosensitive resin composition layer on a workpiece using a hot roll laminator.
[0005] However, the above-mentioned method has the drawback that the surface of the workpiece needs to be heated to a high temperature, which is highly dangerous and complicated. In addition, when the surface of the workpiece is curved or the workpiece has a three-dimensional shape, it is difficult to thermocompress the photosensitive resin composition layer onto the workpiece heated to an arbitrary temperature using a rubber roller, or to thermocompress the photosensitive resin composition layer onto the workpiece using a hot roll laminator.
[0006] On the other hand, as a method for providing a photosensitive resin composition layer on the surface of a workpiece without heating the surface of the workpiece to a high temperature, a laminate having a substrate having adhesive properties on at least a pair of opposing surfaces and a photosensitive resin layer provided on one surface of the substrate is known. For example, Patent Document 4 exemplifies an acrylic adhesive as an adhesive layer provided on a pair of opposing surfaces of a support. Patent Document 5 discloses an image forming method in which a pressure-sensitive adhesive containing a thermoplastic resin and a rosin ester tackifier (thickening agent) is applied to the surface of a polycarbonate resin material, which is a workpiece material, and an image mask is formed thereon, followed by sand etching.
[0007] The above-mentioned adhesive layer and pressure-sensitive adhesive are required to have a good adhesive strength that prevents the image mask from peeling off during sandblasting, for example, in applications such as the manufacture of glass substrates that can be used for protective panels and touch panels for electronic equipment, and the like, so that the image mask does not peel off during sandblasting even when the dot pattern has a diameter of 500 μm or less. On the other hand, the adhesive in the non-masked portion is required to be easily removable after sandblasting, and to have excellent image adhesion that does not peel off the fine image pattern (e.g., dot pattern) when the adhesive in the non-masked portion is removed. Therefore, an adhesive that can meet all of these requirements simultaneously is required. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 06-161098 [Patent Document 2] Japanese Patent Application Publication No. 08-054734 [Patent Document 3] Japanese Patent Application Publication No. 10-239840 [Patent Document 4] JP 2008-183772 A [Patent Document 5] JP 2009-125824 A Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide an adhesive that can firmly hold a mask pattern formed of fine dots, which is produced using a photosensitive resin composition, on a workpiece, and that can easily dissolve and remove only the adhesive in the unmasked areas with water. [Means for solving the problem]
[0010] The above-mentioned problems are solved by the following invention. (1) An adhesive used when adhering a mask material for sandblasting to a workpiece, the adhesive comprising at least a hydrophilic polymer (A) and a plasticizer (B) having two or more hydroxyl groups in the molecule. (2) The adhesive according to the above (1), wherein the hydrophilic polymer (A) is polyvinylpyrrolidone or a vinylpyrrolidone / vinyl acetate copolymer. Effect of the Invention
[0011] According to the present invention, it is possible to provide an adhesive that can firmly hold a mask pattern formed of fine dots on a workpiece using a photosensitive resin composition, and that can easily dissolve and remove the adhesive in the unmasked areas with water. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below. The adhesive of the present invention is an adhesive used when adhering a mask material for sandblasting to a workpiece, and is characterized by containing at least a hydrophilic polymer (A) and a plasticizer (B) having two or more hydroxyl groups in the molecule.
[0013] <Hydrophilic polymer (A)> Examples of the hydrophilic polymer (A) include polyvinyl alcohol, polyethylene glycol, starch, dextrin, carboxymethyl cellulose, polyvinylpyrrolidone, and polyacrylic acid ester resins, as well as derivatives thereof.
[0014] The hydrophilic polymer (A) may also be a copolymer (binary copolymer) or a terpolymer (ternary copolymer) containing, as a monomer, at least one compound selected from the group consisting of vinyl alcohol, ethylene glycol, vinylpyrrolidone, vinyl acetate, dimethylaminopropyl methacrylamide, and methacryloylaminopropyl lauryl dimethylammonium chloride. Examples of copolymers include, for example, vinylpyrrolidone / vinyl acetate copolymers. Examples of terpolymers include vinylpyrrolidone / dimethylaminopropyl methacrylamide / methacryloylaminopropyl lauryl dimethylammonium chloride terpolymers.
[0015] The hydrophilic polymer (A) is preferably polyvinylpyrrolidone or a vinylpyrrolidone / vinyl acetate copolymer.
[0016] In the vinylpyrrolidone / vinyl acetate copolymer, the mass ratio of vinylpyrrolidone (VP) to vinyl acetate (VA) (VP:VA) is preferably 9:1 to 1:9, and more preferably 6:4 to 4:6.
[0017] The number average molecular weight of the hydrophilic polymer (A) is preferably from 1,000 to 3,000,000, more preferably from 5,000 to 1,000,000, further preferably from 10,000 to 500,000, and most preferably from 15,000 to 100,000. The number average molecular weight of the hydrophilic polymer (A) can be measured, for example, by gel permeation chromatography using the following apparatus and conditions. Equipment: Shodex GPC-101 type (Resonac Corporation product) Column: KF-80M x 3 Eluent: THF 1ml / min Temperature: 40℃ Standard material: polystyrene
[0018] <Plasticizer (B)> The plasticizer (B) has two or more hydroxyl groups in the molecule. Examples of the plasticizer (B) include compounds such as 1,2-ethanediol (ethylene glycol), 1,3-propanediol (propylene glycol), 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,2,3-propanetriol (glycerin), and triethanolamine, as well as oligomers and polymers containing these as monomers. These may be used alone or in combination of two or more. Examples of the oligomers and polymers include polyethylene glycol, diglycerin, polyglycerin, dipropylene glycol, tripropylene glycol, polypropylene glycol, and polypropylene glycol glyceryl ether.
[0019] As the plasticizer (B), polypropylene glycol glyceryl ether or 1,5-pentanediol is preferred.
[0020] The number of hydroxyl groups in the molecule of the plasticizer (B) may be 2 or more, preferably 2 to 5, and more preferably 2 to 3.
[0021] In this specification, the intramolecular hydroxyl group does not include a hydroxyl group constituting a carboxy group (-COOH).
[0022] The molecular weight of the plasticizer (B) is preferably less than 1,000. When the plasticizer (B) is a mixture of a plurality of compounds having different molecular weights, the number average molecular weight of the mixture is regarded as the molecular weight of the plasticizer (B). The number average molecular weight of the mixture can be measured using the same device and under the same conditions as those for the hydrophilic polymer (A).
[0023] The ratio of the mass of the hydrophilic polymer (A) to the total mass of the hydrophilic polymer (A) and the plasticizer (B) is preferably from 20 to 95% by mass. In addition, the ratio of the mass of the hydrophilic polymer (A) to the total mass of the hydrophilic polymer (A) and the plasticizer (B) is more preferably 35 mass% or more from the viewpoint of achieving both adhesiveness and selective removability, and more preferably 85 mass% or less for the same reason. In this specification, the mass proportion of each component is defined as the mass proportion of the solid content.
[0024] The ratio of the mass of the plasticizer (B) to the total mass of the hydrophilic polymer (A) and the plasticizer (B) is preferably from 5 to 75% by mass. In addition, the ratio of the mass of the plasticizer (B) to the total mass of the hydrophilic polymer (A) and the plasticizer (B) is more preferably 15 mass% or more from the viewpoint of selective removability, and more preferably 65 mass% or less from the viewpoint of achieving both good adhesion and selective removability.
[0025] The adhesive of the present invention may contain "other components" other than the above-mentioned hydrophilic polymer (A) and plasticizer (B). Examples of "other components" include inorganic solvents (e.g., water), organic solvents (e.g., ethanol), colorants (dyes and pigments), thermal color-developing inhibitors, fillers, defoamers, flame retardants, adhesion promoters, leveling agents, peeling promoters, antioxidants, fragrances, heat curing agents, water repellents, and oil repellents, each of which may be contained in an amount of about 0.01 to 90% by mass relative to the mass of the adhesive. These components may be used alone or in combination of two or more.
[0026] The adhesive of the present invention preferably contains the hydrophilic polymer (A) and the plasticizer (B) in a total amount of 10% by mass or more.
[0027] The adhesive of the present invention may contain, for example, 10 to 90% by mass of a mixed solvent of an inorganic solvent and an organic solvent. The mixing ratio of the inorganic solvent and the organic solvent is not particularly limited, but for example, a mixed solvent of inorganic solvent:organic solvent=1:9 to 9:1 (mass ratio) can be used.
[0028] The adhesive of the present invention can be used when adhering a mask material for sandblasting to a workpiece. As a mask material for sandblasting, a dry film having a photosensitive resin layer on a support such as a polyester film, with a cover film attached onto the photosensitive resin layer, can be used. The workpiece may be made of any material such as glass, stone, metal, plastic, or ceramic, and its shape is not particularly limited. EXAMPLES
[0029] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0030] <Preparation of mask material for sandblasting> Negative dry film resist MS8050 (product name, Mitsubishi Paper Mills, Ltd.), which is commercially available as a photosensitive resin composition, was prepared and exposed through a photomask to an image having pattern regions A to D with dot diameters described below. The negative dry film resist MS8050 has a photosensitive layer (thickness 45 μm), a peeling layer (thickness 2 μm), and a carrier film (polyethylene terephthalate film having a thickness of 25 μm) on a release film (polyethylene terephthalate film) having a thickness of 75 μm, in that order, and exposure was performed from the side having the carrier film. After exposure, the carrier film of the MS8050 was peeled off to expose the release layer, and then alkaline development was carried out with a 0.2% aqueous sodium carbonate solution to obtain a mask material for sandblasting treatment, which has, on the release film, pattern area A formed with dots having a dot diameter of 200 μm, pattern area B formed with dots having a dot diameter of 300 μm, pattern area C formed with dots having a dot diameter of 400 μm, and pattern area D formed with dots having a dot diameter of 500 μm.
[0031] <Preparation of adhesive> (Examples 1 to 8 and Comparative Examples 1 to 4) A hydrophilic polymer (A) and a plasticizer (B) shown in Table 1 below were mixed into a solution obtained by mixing water and ethanol in a 1:1 ratio, and the total solids concentration of the hydrophilic polymer (A) and the plasticizer (B) was adjusted to 20 mass % to obtain the adhesives of Examples 1 to 8 and Comparative Examples 1 to 4. The amounts of hydrophilic polymers (A-1) and (A-3) are shown as the amounts of the solutions (amounts of solids) in Table 1. In Example 1, 70 parts by mass of (A-1) with a solid content of 50% by mass was used, so the amount of solids was 35 parts by mass.
[0032] <Adhesion of masking material for sandblasting> Each of the obtained adhesives was applied to a 3 mm thick glass surface with a brush, and then dried at room temperature for 20 minutes to remove the solvent component and provide an adhesive layer on the glass surface. Then, the surface of the previously prepared sandblasting mask material having the pattern regions A to D was bonded to the surface of the 3 mm thick glass surface having the adhesive layer.
[0033] [Table 1]
[0034] The components listed in the table are as follows. Hydrophilic polymer (A) (A-1) W-635 (trade name, Ashland Corporation, vinylpyrrolidone / vinyl acetate (VP:VA=60:40) copolymer, number average molecular weight 15,000 to 27,000, 50% by weight aqueous solution) (A-2) K-30 (trade name, Ashland Corporation, polyvinylpyrrolidone, number average molecular weight 66,800) (A-3) Styleze W-20 (trade name, Ashland Corporation, vinylpyrrolidone / dimethylaminopropyl methacrylamide / methacryloylaminopropyl lauryl dimethylammonium chloride terpolymer, number average molecular weight 2,700,000, 20% by weight aqueous solution)
[0035] Plasticizer (B) (B-1) Polypropylene glycol glyceryl ether (number average molecular weight: 300, number of hydroxyl groups in the molecule: 3) (B-2) 1,5-pentanediol (molecular weight 104, number of hydroxyl groups in the molecule: 2) (B-3) Uniox (registered trademark) M-550 (product name, NOF Corporation, polyoxyethylene monomethyl ether, number average molecular weight 550, number of hydroxyl groups in molecule: 1) (B-4) Butyl diglycol (molecular weight 162, number of hydroxyl groups in the molecule: 1) (B-5) Uniox (registered trademark) MM-400 (trade name, NOF Corporation, polyoxyethylene dimethyl ether, number average molecular weight 400, number of hydroxyl groups in the molecule: 0) Incidentally, (B-3), (B-4) and (B-5) all have less than two hydroxyl groups in their molecules and therefore do not fall under the category of the plasticizer (B) constituting the adhesive of the present invention.
[0036] <Evaluation of removability, selective removability and adhesion of non-masked areas> (Examples 1 to 5) When the release film of the masking material attached using the adhesive of Examples 1 to 5 was peeled off and washed with running water for 10 seconds, the adhesive of the non-masked portion could be removed without peeling off all of the dot patterns of pattern area A formed by dots with a dot diameter of 200 μm, pattern area B formed by dots with a dot diameter of 300 μm, pattern area C formed by dots with a dot diameter of 400 μm, and pattern area D formed by dots with a dot diameter of 500 μm. Therefore, the removability and selective removability of the non-masked portion were both evaluated as "○". Next, a sandblasting treatment was carried out, which resulted in good processing. Therefore, it was determined that the adhesive strength between the glass surface and the mask material was sufficient, and the adhesiveness was evaluated as "good." Finally, after immersion in water for 1 minute, the mask could be easily peeled off.
[0037] (Examples 6 to 8) When the release film of the masking material attached using the adhesive of Examples 6 to 8 was peeled off and washed with running water for 10 seconds, only the dot pattern of pattern area A formed by dots with a dot diameter of 200 μm peeled off, but the adhesive of the non-masked areas could be removed without peeling off of the other pattern areas (pattern area B, pattern area C, and pattern area D). Therefore, the removability of the non-masked areas was evaluated as "○" and the selective removability was evaluated as "△". Next, a sandblasting treatment was carried out, which resulted in good processing. Therefore, it was determined that the adhesive strength between the glass surface and the mask material was sufficient, and the adhesiveness was evaluated as "good." Finally, after immersion in water for 1 minute, the mask could be easily peeled off.
[0038] (Comparative Examples 1 to 4) When the release film of the mask material attached using the adhesive of Comparative Examples 1 to 4 was peeled off, the dot patterns in all areas (pattern area A, pattern area B, pattern area C and pattern area D) peeled off, the desired pattern could not be formed, and washing with running water and sandblasting treatment could not be performed. The masking material came off when the release film was peeled off, so there was no need to perform sandblasting, and the adhesion was rated as "x." In addition, because rinsing with running water was not performed, the removability and selective removability of the unmasked areas were not evaluated (rated "-").
[0039] From the above results, it was confirmed that the adhesive of the present invention has good adhesion properties that prevent the mask material from peeling off during sandblasting, even for fine dot patterns with a diameter of 500 μm or less, that the adhesive in the unmasked areas can be easily removed, and that the fine image pattern does not peel off when the unmasked areas are removed. [Industrial Applicability]
[0040] The adhesive of the present invention can be particularly suitably used when adhering a mask material for sandblasting to a workpiece.
Claims
1. An adhesive used when adhering a mask material for sandblasting to a workpiece, the adhesive comprising at least a hydrophilic polymer (A) and a plasticizer (B) having two or more hydroxyl groups in the molecule.
2. 2. The adhesive of claim 1, wherein the hydrophilic polymer (A) is polyvinylpyrrolidone or a vinylpyrrolidone / vinyl acetate copolymer.
Citation Information
Patent Citations
Photosensitive resin composition for sand blasting and photosensitive film formed by using the same
JP1994161098A
Photosensitive resin composition and photosensitive dry film using the same
JP1996054734A
Photosensitive resin composition for sandblast and its use
JP1998239840A
Laminate, mask for sand blasting and treatment method of base material to be processed
JP2008183772A
Method of forming image by sand etching
JP2009125824A